Peran Guru Pembimbing dalam Membina Komunikasi Interpersonal Peserta Didik di SMK Negeri 4 Padang (Jurusan Bimbingan dan Konseling Islam, 2020)
The purpose of this study was to determine the form of interpersonal communication of students, the efforts of the mentor teacher in fostering student communication through the provision of information services and the provision of individual services, and the efforts of the obstacles faced by teachers of SMK Negeri 4 Padang. This research is a field research (Field Research). ) with a descriptive research method, which describes the role of the mentor teacher in fostering communication of students at SMK Negeri 4 Padang. Based on this research, it was found that the form of interpersonal communication carried out by students at school was in the form of verbal communication and non-verbal communication. The effort of the supervising teacher in fostering student communication is by providing information services about communication procedures and individual counseling services. Constraints faced by supervisors in fostering student communication are the lack of time the supervisor has to carry out guidance and counseling activities, the number of tutors who are not proportional to the number of students, the number of tasks other than the guidance and counseling duties.